Indigenous Food and Culture in Iranshahr, Balochistan Indigenous Food and Culture in Iranshahr, Balochistan (Case Study: The Village of Damen) - Asghar Asgari Khaneghah; Atiyeh Azarshab; Behrouz Roustakhiz (Dānishhā-yi būmī-i Īrān, 2017)
The present paper studies the local and traditional food system of Baloch residents in Damen. The purpose of this study is to describe the food system of these people, determine and evaluate its constitutive elements and mechanisms existing in this traditional food system. The present study has been carried out using the qualitative method of ethnography and in it the techniques such as interviews, observation and participatory observation have been used. Our study in this traditional system represents a significant impact on the natural environment of residents, as well as the involvement of cultural and social factors in shaping a native food system in this region. In fact, in this close relationship between food and natural, cultural, social and economic factors, a set of concepts is constantly produced and reproduced, which eventually led to the identification of local cuisine and village residents. In general, by examining the whole mentioned factors, some kind of food culture has become prominent among the people of the village, which has been the basis for identifying and distinguishing this people from other parts.